Signs of an Enmeshed Relationship: Motivations and Outcomes of Social Networking Sites Password Sharing among Emerging Adult Men - J.P.G. Gutierrez; A.J.D. Aledia; G.G. Guevarra; J.R.A. Jasa; D.M. Villanueva; K.S. Tan (Социальная психология и общество)
Objectives. The purpose of the study is to provide depth and analysis in understanding the reasons and outcomes of password sharing in the context of men's perception. The study will show a general idea of what phenomenon could occur if emerging adults decide to share a password with their partner. Background. The campaign on securing one’s own password on one’s social media accounts has supposedly reached everyone. However, emerging adult men do share their password, either they initiated the password sharing or as a response to their partner’s demands. Despite the status of couples sharing passwords, there is a dearth of study exploring the reasons and perceived consequences of emerging adult men on password sharing. Study design. This study investigated the phenomenon of password sharing among emerging adult men’s heterosexual relationships, thus a phenomenological design was used. Themes were extracted from interview transcripts via theoretically flexible thematic analysis. Participants. 20 male heterosexual adult Filipinos aged (21 to 24 years old) who are in monogamous relationships (M = 22,3; SD = 0,73). Measurements. Semi-structured interview was used in the data collection. With the elements of both structured and unstructured interview, the researchers garnered comparable and reliable data while also being able to pose extra queries to gain deeper insight about password sharing. Results. The researchers found that the sharing of passwords between couples can be motivated by both personal and relational motivators. Furthermore, it was also found that password sharing in relationships has both detrimental impact and constructive consequences on their relationship and their own personal lives. Conclusion. This study entails that password sharing, as have been foreseen by agencies that campaigns for it, has its detrimental consequences both for the relationship and their personal boundaries. Nonetheless, password sharing had constructive consequences such as relief from relationship anxieties, and increased understanding of their partner’s social circles.